A Different World: Enduring Effects of School Desegregation on Ideology and Attitudes - Ethan Kaplan; Jörg L. Spenkuch; Cody Tuttle (CESifo GmbH, 2025)
In 1975, a federal court ordered the desegregation of public schools in Jefferson County, KY. In order to approximately equalize the share of minorities across schools, students were assigned to a busing schedule that depended on the first letter of their last name. We use the resulting quasi-random variation to estimate the long-run impact of attending an inner-city school on political participation and preferences among whites. Drawing on administrative voter registration records and an original survey, we find that being bused to an inner-city school significantly increases support for the Democratic Party and its candidates more than forty years later. Consistent with the idea that exposure to an inner-city environment causes a permanent change in ideological outlook, we also find evidence that bused individuals are much less likely to believe in a "just world" (i.e., that success is earned rather than attributable to luck) and, more tentatively, that they become more supportive of some forms of redistribution. Taken together, our findings point to a poverty-centered version of the contact hypothesis, whereby witnessing economic deprivation durably sensitizes individuals to issues of inequality and fairness.
Keywords: H00; P00; J00; N00; 330; ideology; inequality; school desegregation; busing